The relationships between social media use, time management, and decision-making styles - Şıngır, Hatice (Frontiers in Psychology, 2025)
The present study examined the relationship between social media use, time management, and decision-making styles. The sample consisted of 612 participants, including 513 women (83.8%) and 99 men (16.2%), who were university students and young adults. Data were collected using a personal information form (age, gender, social media usage time, and academic achievement), the Time Management Scale, and the Melbourne Decision-Making Questionnaire. In addition to these measures, differences were analyzed concerning age, gender, academic achievement, and duration of social media use. Descriptive statistics, independent samples t-tests, one-way analysis of variance (ANOVA), chi-square tests, and regression analyses were employed in data analysis. The results indicated that female participants scored significantly higher than males on overall time management, time planning, and time wasters subscales. In contrast, male participants obtained significantly higher scores on the time attitude subscale. Furthermore, the self-esteem and hypervigilance subscales of the decision-making scale differed by gender; female participants reported lower self-esteem and higher hypervigilance scores compared to their male counterparts. Academic achievement was positively associated with time management skills, such that higher academic performance predicted better time management. Social media use was negatively and significantly associated with overall time management and all its subscales. In contrast, it was positively associated with buckpassing, procrastinatory, and hypervigilance decision-making styles and negatively associated with the careful decision-making style. A positive relationship was also identified between overall time management and decision-making styles. Specifically, individuals with better time management skills demonstrated higher self-esteem and a tendency toward careful decision-making, whereas negative associations were observed with buckpassing, procrastinatory, and hypervigilance styles. Finally, longer durations of social media use significantly predicted lower self-esteem, careful decision-making, and higher levels of buckpassing, procrastinatory, and hypervigilance decision-making styles.